SURGICAL TREATMENT OF RADIATION-INDUCED ANTERIOR CHEST WALL OSTEOSARCOMA AFTER BREAST CARCINOMA: A CASE REPORT - Čičić, Stevan; Ristanović, Aleksandar; Prcović, Mladen; Marić, Nebojša; Savić, Mlađana (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Radiotherapy for breast cancer can rarely lead to radiation-induced osteosarcoma (RIOS), a highly aggressive malignancy. This article aims to present the specificity of the surgical treatment applied and the level of aggressiveness of this rare malignant tumor. Case report: A 63-year-old female patient was admitted to the Chest Surgery Department of the Military Medical Academy due to a large exulcerated sternal mass releasing a purulent secretion, initially misdiagnosed as recurrent breast carcinoma 15 years post-treatment, and anemia. Biopsy confirmed high-grade osteosarcoma following prior radiotherapy. After metastasis was ruled out, the patient received neoadjuvant chemotherapy and underwent radical resection of the sarcoma, sternum, anterior III–VII ribs, and adjacent soft tissues. Chest wall reconstruction was achieved using titanium bars, clips, and a latissimus dorsi myocutaneous flap. Upon local recurrence, further resection of the manubrium and anterior II ribs, with soft tissues, was performed. A year after the initial operation, a suspicious subcutaneous mass in the left pectoral region was excised for histopathological analysis.  Conclusion: RIOS of the chest wall exhibits a more aggressive course and worse prognosis than sporadic chest wall sarcomas, with higher rates of recurrence despite wide resection, as demonstrated in this case. Reconstruction with titanium bars and clips, after extensive anterior chest wall resection, provides a rigid and feasible alternative for restoring stability. This case underscores the importance of recognizing RIOS as a rare but serious late complication of breast cancer radiotherapy and highlights the complexity and specificity of surgical management and reconstruction for optimal outcomes.
Keywords: sternal mass; resection; rigid reconstruction; titanium bars; titanium clips; myocutaneous flap; soft tissue reconstruction